KUALITAS TIDUR PADA MAHASISWA TINGKAT AKHIR (STUDI KASUS: PERBANDINGAN MAHASISWA PROGRAM STUDI ILMU ALAM DAN SOSIAL) - Bera Liwun, Stephanus Benedictus; Mulyanto, Tri; Avian, Noor Kurnia; Chrisnatalia, Maria (Universitas Gunadarma, 2024)
Sleep is one of the basic human needs and plays a role in physical and mental health and quality of life. Lack of sleep tends to cause decreased concentration, fatigue, and decreased productivity, and students tend to have poor sleep quality due to stress from lectures and writing a thesis. The purpose of this study was to examine the differences in sleep quality of students when writing a thesis which were reviewed based on the scientific field they had. This study used a quantitative method by using the Pittsburgh Sleep Quality Index (PSQI) in Indonesian as a measurement sleep quality. The respondents in this study were 200 students obtained through purposive sampling techniques. The results showed that there was no difference in the sleep quality of final year students in the natural and social sciences. The level of stress felt by final year students in both scientific fields due to the pressure of the final thesis assignment seemed to be the reason why there was no difference in the quality of sleep they had.